Peningkatan Motivasi Belajar Matematika Siswa Melalui Model Pembelajaran Kooperatif Tipe Teams Assisted Individualization (TAI) pada Siswa Kelas XI IPS 1 SMA Negeri 6 Kerinci - Maisun Maisun (Universitas Batanghari Jambi, 2021)
This research was a classroom action research. The study was conducted because there were some students who were lack of motivation in learning Math Subject. Therefore, the researcher offered Cooperative Team Assisted Individualization (TAI) to improve the students learning motivation on Math Subject. The objective of the research was to figure out whether the method could improve the student’s learning motivation related to cooperation, participation, passion and learning enthusiasm at grade XII IPS 1 SMA N 1 Kerinci. The collaborator of the research was a teacher who taught the same subject. The research was done in two cycles which had three stages; (a) Planning (b) Action (c) Observation, and (d) Reflection. The data were collected by using (a) observation (b) Questionnaire (c) Written test. The data analysis result showed that the student’s learning motivation in Math subject improved significantly after Cooperative TAI (Teams Assisted Individualization) was implemented. The student’s learning motivation in cycle one was 58,69%, then in cycle 2 the percentage was 75,30%. It concluded that the implementation of Cooperative TAI in learning and teaching process on Math Subject improved the student’s learning motivation. It was suggested to Math Teacher to apply this method as one of the solutions to cover the student’s learning motivation problem on Math Subject.